Family picture a study on the influence of news media on the voting public's perceived image of political dynasties in the province of Nueva Ecija - Rosario, Jeannica Mae Martin 1993- (2014)
"This study aims to discover how the news media contributes to the voting public's formation of their perceived image regarding political dynasties. McComb's Agenda-setting theory and Muzaref Sherif's Social Judgment theory are the study's theoretical anchors. A quantitative approach is used in order to generalize descriptive results to the province. Specifically, content analysis and interviewer-administered surveys are employed. Results of the study show that the media and the residents of Nueva Ecija do not have the same image of dynastic politicians. Despite this, the news media can still influence the public's perception of the issue through the amount the saliency it allots to political dynasty news. Moreover, the Internet contains more in-depth information about dynasties more often than television news. Despite the political context of the province, the residents do not see political dynasties as an issue that directly affects their lives, but more of a national concern. This is due to the low political engagement and discussion by the voters. Because of this, the residents tend to know more national dynasties than local ones and see dynastic politicians as personalities and not by their issue positions."